Analysis of flap sugar as an objective monitoring of intra-operative flap vascularity following a single vein vs. a double vein anastomosis - Sindhuja, A; Sahu, S A; Mishra, J K; Saha, A; Rahmi, J J; Valsalan, A (Acta chirurgiae plasticae, 2025)
INTRODUCTION: Venous thrombosis is a common cause of flap failure. Performing a second vein anastomosis provides a backup channel for draining. However, this may not be useful in circumstances of vessel kinking and compression. When a flap is compromised, there is a decrease in glucose levels and an increase in anabolic metabolites like lactate. In our study, we measured the ratio of flap/peripheral sugar levels (glucose index - GI) as a metabolic indicator and assessed flap perfusion after the second vein anastomosis. MATERIALS AND METHODS: This was a single-centre prospective cohort study. Based on the inclusion criteria, eligible patients reconstructed with a free flap (anterolateral thigh flap / radial forearm flap / fibula flap) were included in the study. RESULTS: In our series, the mean flap sugar levels after the first and the second vein anastomoses were 116.60 mg/dL and 131.5 mg/dL, respectively. There was an increase in the flap sugar level after the second vein anastomosis. This increase was found statistically significant (P = 0.009), suggestive of better perfusion. In this study, the flap/peripheral glucose level (GI) ratios after the first and the second vein anastomoses were 0.90 and 0.99, respectively. The increase in this ratio after the second vein anastomosis indicated better flap perfusion after a double vein anastomosis. CONCLUSION: The study concluded that there is a better perfusion after a double vein anastomosis.
Keywords: vény; free flap; Male; flap metabolism; Adult; Free Tissue Flaps; Prospective Studies; dospělí; mužské pohlaví; senioři; Aged; Plastic Surgery Procedures; single vein vs. double vein anastomosis; anastomóza chirurgická; volné tkáňové laloky; lidé; ženské pohlaví; Humans; flap sugar; zákroky plastické chirurgie; Anastomosis, Surgical; peripheral sugar; Veins; Female; lidé středního věku; Middle Aged; prospektivní studie